Joint Impact of Financial Performance and Corporate Social Responsibility on Firm Value: Does Legitimacy Matter? - Fransiskus Eduardus Daromes; Suwandi Ng; Korina P. Legaspi (Indonesian Journal of Sustainability Accounting and Management, 2023)
The purpose of this study is to examine the effect of the interaction of financial performance and corporate social responsibility disclosure on firm value. The research model was constructed from the theory of legitimacy and used a purposive sampling method. The companies in the sample were non-financial companies listed on the Indonesian Stock Exchange for the period 2017-2019 that disclose annual and sustainable development reports respectively. Analysis of data by moderate regression analysis. The results of this study indicated that neither financial performance nor corporate social responsibility had a significant effect on firm value. On the other hand, the interaction between financial performance and disclosure of corporate social responsibility had a significant positive effect on firm value. Furthermore, the implications of the research both theoretically and practically have been discussed.